“The despicable rank of a theatrical versifier”: Alexander Sumarokov and Giuseppe Bonechi - Дёмин, Антон (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The paper examines the mention of Giuseppe Bonechi made by Alexander Sumarokov in his letter to count Shuvalov dated the 12th March 1761 in the context of the quarrel with count Sievers and of Sumarokov’s dismissal from theatre and from service. The expression “the despicable rank of a theatrical versifier” is interpreted in the light of Bonechi’s social position as a subordinate in the court’s Italian troupe, while Sumarokov aspires to a leading position in the Russian company. The artistic relationship of Sumarokov and Bonechi is examined from the point of view of the competition between the Italian and the Russian company at the court. Bonechi’s dismissal in 1752 was less painful than that of Sumarokov in 1761 because the Italian could easily find a place at any European court as a man of theatre, while Sumarokov, having created the unique Russian national theatre, was considerably more vulnerable due to his social position.